2012
DOI: 10.1261/rna.029876.111
|View full text |Cite
|
Sign up to set email alerts
|

Both Sm-domain and C-terminal extension of Lsm1 are important for the RNA-binding activity of the Lsm1–7–Pat1 complex

Abstract: Lsm proteins are a ubiquitous family of proteins characterized by the Sm-domain. They exist as hexa-or heptameric RNAbinding complexes and carry out RNA-related functions. The Sm-domain is thought to be sufficient for the RNA-binding activity of these proteins. The highly conserved eukaryotic Lsm1 through Lsm7 proteins are part of the cytoplasmic Lsm1-7-Pat1 complex, which is an activator of decapping in the conserved 59-39 mRNA decay pathway. This complex also protects mRNA 39-ends from trimming in vivo. Puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 40 publications
4
36
0
Order By: Relevance
“…This may partly be to do with the smaller size of the Lsm1-7 complex compared with the wild-type Lsm1-7-Pat1 complex (∼97 kD vs. ∼185 kD). Second, while the Lsm1-7-Pat1 complex clearly exhibited a higher affinity for the PGK1-A 5 RNA than the PGK1 RNA as expected and as observed earlier (Chowdhury and Tharun 2009;Chowdhury et al 2012), such binding preference could not be observed with the Lsm1-7 complex. Very similar results were also observed when the experiments were carried out using the MFA2 and MFA2-A 5 RNAs (42-mer RNA derived from the 3 ′ UTR of MFA2 and the 3 ′ -penta-adenylated version of such RNA) as substrates for gel shift assays (Fig.…”
Section: Lsm1-7 Complex Assembles In Pat1δ Cellssupporting
confidence: 78%
See 4 more Smart Citations
“…This may partly be to do with the smaller size of the Lsm1-7 complex compared with the wild-type Lsm1-7-Pat1 complex (∼97 kD vs. ∼185 kD). Second, while the Lsm1-7-Pat1 complex clearly exhibited a higher affinity for the PGK1-A 5 RNA than the PGK1 RNA as expected and as observed earlier (Chowdhury and Tharun 2009;Chowdhury et al 2012), such binding preference could not be observed with the Lsm1-7 complex. Very similar results were also observed when the experiments were carried out using the MFA2 and MFA2-A 5 RNAs (42-mer RNA derived from the 3 ′ UTR of MFA2 and the 3 ′ -penta-adenylated version of such RNA) as substrates for gel shift assays (Fig.…”
Section: Lsm1-7 Complex Assembles In Pat1δ Cellssupporting
confidence: 78%
“…The ability of the Lsm1-7-Pat1 complex to bind RNA and to recognize the presence of the 3 ′ oligo(A) tail of the RNA is essential for mRNA decay in vivo as revealed by our past analysis of various lsm1 mutants (Tharun et al 2005;Tharun 2008, 2009;Chowdhury et al 2012). However, the contribution of Pat1 to the RNA binding properties of the Lsm1-7-Pat1 complex is not known.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations